Unveiling the Secrets of Qur’anic Revelation: A Study of Its Stages, Intermediaries, and Modes of Receiving Revelation - Muh. Imam Hidayat; Andi Miswar; Halimah Basri (TAFASIR: Journal of Quranic Studies, 2026)
The phenomenon of Qur’anic revelation represents a multidimensional process encompassing theological, cosmological, and communicative-historical aspects. This study aims to provide a comprehensive analysis of the stages of revelation, the angelic mediation involved, and the various modes through which the Prophet Muhammad ﷺ received divine messages, including the concept of sab‘ah aḥruf (seven modes). Using a qualitative method with a library research approach and descriptive-analytical analysis, this paper examines both classical and contemporary sources such as al-Suyūṭī, al-Zarqānī, and Manna‘ al-Qaṭṭān. The findings reveal three main stages of revelation: its inscription in the Lauḥ al-Maḥfūẓ (Preserved Tablet), its descent to Bayt al-‘Izzah, and its gradual transmission to the Prophet through the Angel Jibrīl over 23 years. The Prophet experienced revelation in diverse forms—true dreams, divine inspiration to the heart, sounds resembling ringing bells, the angel’s appearance in human form, and direct communication with God. Furthermore, the concept of sab‘ah aḥruf illustrates the linguistic flexibility of the Qur’an, providing ease for diverse Arab dialects. This research concludes that revelation is not merely a vertical transmission of divine text but a structured divine-human communication process, enriching contemporary Qur’anic studies.